2004
DOI: 10.3310/hta8410
|View full text |Cite
|
Sign up to set email alerts
|

Provision, uptake and cost of cardiac rehabilitation programmes: improving services to under-represented groups

Abstract: Non-UK purchasers will have to pay a small fee for post and packing. For European countries the cost is £2 per monograph and for the rest of the world £3 per monograph.You can order HTA monographs from our Despatch Agents:-fax (with credit card or official purchase order) -post (with credit card or official purchase order or cheque) -phone during office hours (credit card only).Additionally the HTA website allows you either to pay securely by credit card or to print out your order and then post or fax it. NHS … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
153
0
5

Year Published

2007
2007
2017
2017

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 221 publications
(160 citation statements)
references
References 104 publications
(216 reference statements)
2
153
0
5
Order By: Relevance
“…In addition, the majority of previous economic analyses had a more intensive centre-based programme than are standard in the UK 28,29,31,95,97,98 and had less home visiting than was provided in this study. 100 Although the cost per patient in the centre-based arm in BRUM was lower than in the HTA survey 63 (£157 in BRUM versus £220 per patient referred), much of this difference is due to the BRUM centrebased costs including a narrower range of services and focusing on Phase III of the CR programme whereas the HTA survey included the whole CR service costs divided between the number of CR participants. This will include the phase one input to all patients, some Phase II home visiting programmes and some Phase IV continuation programmes.…”
Section: Economic Study Findingsmentioning
confidence: 95%
See 2 more Smart Citations
“…In addition, the majority of previous economic analyses had a more intensive centre-based programme than are standard in the UK 28,29,31,95,97,98 and had less home visiting than was provided in this study. 100 Although the cost per patient in the centre-based arm in BRUM was lower than in the HTA survey 63 (£157 in BRUM versus £220 per patient referred), much of this difference is due to the BRUM centrebased costs including a narrower range of services and focusing on Phase III of the CR programme whereas the HTA survey included the whole CR service costs divided between the number of CR participants. This will include the phase one input to all patients, some Phase II home visiting programmes and some Phase IV continuation programmes.…”
Section: Economic Study Findingsmentioning
confidence: 95%
“…63 Patient factors include work or domestic commitments, 20,39,64,65 a lack of interest in rehabilitation or a reluctance to change their lifestyle, [65][66][67] a dislike of groups, 68 patient depression, 55 living in a rural setting 50,69 and lack of support from the family. 54,65 Difficulties with accessibility of programmes and parking problems are commonly cited as a reason for poor adherence.…”
Section: Reasons For Poor Uptake and Adherencementioning
confidence: 99%
See 1 more Smart Citation
“…A number of studies have found women are less likely to attend CR [14][15][16] but this may be related to women generally being older than men when they present with CHD and because they are also more likely to live alone [17]. In addition, there is some evidence that women tend to have poorer health and significant co-morbidity at presentation compared to men which may be a reason why women are less likely to be offered CR in the first instance [18]. A recent systematic review identifying studies which reported on interventions to improve uptake, adherence and professional compliance in cardiac rehabilitation by Beswick et al identified only two studies which reported interventions in ethnic groups [19]: one of these was a prospective study set in North America and the other was a programme description of a project in the UK providing translated educational material to South Asians.…”
Section: Comparison With Previous Workmentioning
confidence: 99%
“…although this method is not systematic and can be costprohibitive, it is informative to patients and promotes Cr endorsement. 26 there are two published reviews that have examined multiple Cr utilization interventions and their effects on Cr enrollment and adherence, 45,46 but neither investigated effects on Cr referral rates. moreover, the effect of referral strategies on Cr utilization has not been specifically reviewed.…”
Section: Introductionmentioning
confidence: 99%